Comparison of the performances of non-parametric k-sample test procedures as an alternative to one-way analysis of variance - Macunluoglu, Aslı Ceren; Ocakoğlu, Gökhan (The European Research Journal, 2023)
Objectives: The performances of the Kruskal-Wallis test, the van der Waerden test, the modified version of Kruskal-Wallis test based on permutation test, the Mood's Median test and the Savage test, which are among the non-parametric alternatives of one-way analysis of variance and included in the literature, to protect the Type-I error probability determined at the beginning of the trial at a nominal level, were compared with the F test. Methods: Performance of the tests to protect Type-I error; in cases where the variances are homogeneous/heterogeneous, the sample sizes are balanced/unbalanced, the distribution of the data is in accordance with the normal distribution/the log-normal distribution, how it is affected by the change in the number of groups to be compared has been examined on simulation scenarios. Results: The Kruskal-Wallis test, the van der Waerden test, the modified version of the Kruskal-Wallis test based on the permutation test were not affected by the distribution of the data, but by the violation of the homogeneity of the variances. The performance of the Mood's Median test and the Savage test were not found to be sufficient in terms of protection of theType-I error compared to other tests. Conclusions: It was determined that the Kruskal-Wallis test, the van der Waerden test, the modified version of Kruskal-Wallis test based on permutation test were not affected by the distribution of the data and tended to preserve the Type-І error when the variances were homogeneous.